The contribution of geogenic particulate matter to lung disease in indigenous children - Shepherd, C.C.J.; Clifford, H.D.; Mitrou, F.; Melody, S.M.; Bennett, E.J.; Johnston, F.H.; Knibbs, L.D.; Pereira, Gavin; Pickering, J.L.; Teo, T.H.; Kirkham, L.A.S.; Thornton, R.B.; et al. (MDPI, 2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. Indigenous children have much higher rates of ear and lung disease than non-Indigenous children, which may be related to exposure to high levels of geogenic (earth-derived) particulate matter (PM). The aim of this study was to assess the relationship between dust levels and health in Indigenous children in Western Australia (W.A.). Data were from a population-based sample of 1077 Indigenous children living in 66 remote communities of W.A. (>2,000,000 km2), with information on health outcomes derived from carer reports and hospitalisation records. Associations between dust levels and health outcomes were assessed by multivariate logistic regression in a multi-level framework. We assessed the effect of exposure to community sampled PM on epithelial cell (NuLi-1) responses to non-typeable Haemophilus influenzae (NTHi) in vitro. High dust levels were associated with increased odds of hospitalisation for upper (OR 1.77 95% CI [1.02–3.06]) and lower (OR 1.99 95% CI [1.08–3.68]) respiratory tract infections and ear disease (OR 3.06 95% CI [1.20–7.80]). Exposure to PM enhanced NTHi adhesion and invasion of epithelial cells and impaired IL-8 production. Exposure to geogenic PM may be contributing to the poor respiratory health of disadvantaged communities in arid environments where geogenic PM levels are high.